Cases, Mechanisms and the Real: The Theory and Methodology of Mixed-Method Social Network Analysis. (May 2016) - Crossley, Nick; Edwards, Gemma
In this paper we make a methodological case for mixed method social network analysis (MMSNA). We begin by both challenging the idea, prevalent in some quarters, that mixing methods means combining incompatible epistemological or theoretical assumptions and by positing an ontological argument in favour of mixed methods. We then suggest a methodological framework for MMSNA and argue for the importance of 'mechanisms' in relational-sociological research. Finally, we discuss two examples of MMSNA from our own research, using them to illustrate arguments from the paper.